Effect of estrous cycle phases on gene expression in bovine oviduct epithelial cells - Ricaurte Lopera-Vásquez; Fabián Uribe-García; Iang Rondón-Barragán (Veterinary World, 2022)
Background and Aim: The oviduct environment is of particular importance because it is the site of fertilization and early embryo development. The oviduct, as a component of the reproductive system, responds to ovarian hormone (estradiol [E2] and progesterone [P4]) stimuli depending on the estrous cycle phase. This study aimed to elucidate the effect of estrous cycle phases (follicular and early and late luteal phases) on gene expression patterns in bovine oviduct epithelial cells (BOECs).